Prove,by vector method,that the point of intersection of the diagonals of the trapezium lies on the line passing through the mid-points of the parallel sides.

My Attempt:
Let the trapezium be $OABC$ and that the O is a origin and the position vectors of $A,B,C$ be $\vec{a},\vec{b},\vec{c}$.Then the equation of $OB$ diagonal is $\vec{r}=\vec{0}+\lambda \vec{b}................(1)$
And equation of $AC$ diagonal is $\vec{r}=\vec{a}+\mu(\vec{c}-\vec{a}).......(2)$
And the equation of the line joining the mid points of $OA$ i.e.$\frac{\vec{a}}{2}$ and $BC$ i.e. $\frac{\vec{b}+\vec{c}}{2}$ is $\vec{r}=\frac{\vec{a}}{2}+t(\frac{\vec{b}+\vec{c}}{2}-\frac{\vec{a}}{2}).........(3)$.
Here $\lambda,\mu,t$ are scalars.
I do not know how to solve $(1)$ and $(2)$ and put into $(3)$ to prove the desired result.
Please help me.Thanks.


(1) and (2) can be solved for $\mu$ and $\lambda$ by setting $\lambda \vec{b} =\vec{a}+\mu(\vec{c}-\vec{a}) $ and looking at the two coordinates. This gives two equations in two unknowns, and so can be solved. Putting in the values for $\lambda \vec{b} $ gives the coordinates of the point of intersection.

Similarly, equation (3) gives parameterizations for the coordinates of the line. Looking at one of these, say $x$, you can solves for the value of $t$ that gives that $x$ value.

That same value of $t$ should give the $y$ coordinate of the intersection.

I feel that there should be a more purely vector approach, but one does not occur to me right now.

  • $\begingroup$ While solving $\lambda \vec{b}=\vec{a}+\mu(\vec{c}-\vec{a})$.What are the two equations in two unknowns?I do not get this. $\endgroup$ – Vinod Kumar Punia Nov 6 '15 at 6:08
  • $\begingroup$ Look separately at the x and y coordinates. You have $\lambda b_x = a_x+\mu(c_x-a_x)$ and $\lambda b_y = a_y+\mu(c_y-a_y)$. These are your two equations. $\endgroup$ – marty cohen Nov 6 '15 at 6:18

You're missing an additional piece of information: There are two parallel sides to the trapezium. Express this by assuming that $\vec b -\vec c = k\vec a$ for some $k$. You now can solve for $$\vec b = \vec c + k\vec a\,.\tag4$$ Put (4) into the equation (1) = (2) to find $$\mu = \lambda = \frac1{k+1}\,.$$ You then check that with this choice of $\lambda$ and $\mu$, the resulting $\vec r$ satisfies (3). Note that with (4), equation (3) becomes $$ \vec r = t\vec c + \left(\frac {t(k-1)+1}2\right)\vec a\,. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.